PEMBENTUKAN PORTOFOLIO OPTIMAL TIGA SAHAM LQ45 DAN PERBANDINGAN TERHADAP KINERJA REKSA DANA SAHAM PADA OKTOBER 2016 - Hidayat, Erick Saputra (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, Universitas Tarumanagara, 2017)
This study attempts to form an optimal portfolio of three stocks derived from LQ45 stock index and compared with the best stock mutual fund made by investment manager according to realized return from September 2015 to September 2016 with monthly holding period. Optimal portfolio is a portfolio that provides the highest level of expected return for a given level of risk or the lowest risk for a given level of expected return in compare to other portfolios. The method used in this research is sharpe ratio.This research use a software named PORTO which is designed for portfolio investment and created by Edwin J. Elton, Martin J. Gruber, and Christopher R. Blake in 1995. The results of this research showed that the optimal portfolio of three stocks is better than stock mutual fund. The optimal portfolio of three stocks consist of 73.391% stock TLKM, 17.993% stock ADRO, and 8.616% stock LSIP. These combinations are expected to give 54.70% of expected return and 29.50% of risk with 1.654237 of sharpe ratio. The stock mutual fund is Treasure Fund Super Maxxi. This mutual fund are expected to give 40.52% of expected return and 75.85% of risk with 0.456417 of sharpe ratio.Keywords: Optimal portfolio, Mutual fund, Sharpe ratio, PORTO, LQ45